High dose expression of heme oxigenase-1 induces retinal degeneration through ER stress-related DDIT3 - Huirong Li (Molecular Neurodegeneration, 2021)
Abstract Background Oxidative stress is a common cause of neurodegeneration and plays a central role in retinal degenerative diseases. Heme oxygenase-1 (HMOX1) is a redox-regulated enzyme that is induced in neurodegenerative diseases and acts against oxidative stress but can also promote cell death, a phenomenon that is still unexplained in molecular terms. Here, we test whether HMOX1 has opposing effects during retinal degeneration and investigate the molecular mechanisms behind its pro-apoptotic role. Methods Basal and induced levels of HMOX1 in retinas are examined during light-induced retinal degeneration in mice. Light damage-independent HMOX1 induction at two different expression levels is achieved by intraocular injection of different doses of an adeno-associated virus vector expressing HMOX1. Activation of Müller glial cells, retinal morphology and photoreceptor cell death are examined using hematoxylin-eosin staining, TUNEL assays, immunostaining and retinal function are evaluated with electroretinograms. Downstream gene expression of HMOX1 is analyzed by RNA-seq, qPCR examination and western blotting. The role of one of these genes, the pro-apoptotic DNA damage inducible transcript 3 (Ddit3), is analyzed in a line of knockout mice. Results Light-induced retinal degeneration leads to photoreceptor degeneration and concomitant HMOX1 induction. HMOX1 expression at low levels before light exposure prevents photoreceptor degeneration but expression at high levels directly induces photoreceptor degeneration even without light stress. Photoreceptor degeneration following high level expression of HMOX1 is associated with a mislocalization of rhodopsin in photoreceptors and an increase in the expression of DDIT3. Genetic deletion of Ddit3 in knockout mice prevents photoreceptor cell degeneration normally resulting from high level HMOX1 expression. Conclusion The results reveal that the expression levels determine whether HMOX1 is protective or deleterious in the retina. Furthermore, in contrast to the protective low dose of HMOX1, the deleterious high dose is associated with induction of DDIT3 and endoplasmic reticulum stress as manifested, for instance, in rhodopsin mislocalization. Hence, future applications of HMOX1 or its regulated targets in gene therapy approaches should carefully consider expression levels in order to avoid potentially devastating effects.